Isolation and Identification of Hg-Resistant Bacteria as Bioremediator Agents and Their Potential in Reducing Mercury Contamination - SORAYA FITRIA NASIR; ANI M. HASAN; ARYATI ABDUL; YULIANA RETNOWATI (Microbiology Indonesia, 2021)
This study aims to describe Hg-resistant bacteria in soil contaminated with gold mining waste and its ability to reduce mercury contamination. This research was initiated by taking soil samples at the gold processing plant in Ilangata Village, Anggrek District, North Gorontalo Regency. Then the research was carried out at the Microbiology Laboratory of the Biology Department, Faculty of Mathematics and Natural Sciences. Mercury analysis was carried out at the Laboratory of Fisheries Product Quality Development and Testing (LPPMHP) Gorontalo Province and bacterial identification was carried out at the HumRC Research Unit, Faculty of Medicine, Hasanuddin University. The study was conducted from July to October 2020. This study used a descriptive method. The parameters observed were the types of Hg resistant bacteria and the ability of the bacteria to reduce mercury contamination. Data were analyzed descriptively. The results showed that there were four bacterial isolates on the soil contaminated with mercury at 4.5 ppm. Two of them could not be resistant to levels of 10 ppm mercury. However, these four isolates had the ability to reduce mercury levels by 99%. Based on the reconstruction of the phylogenetic tree, bacterial isolate 01 has a close relationship with Stenotrophomonas sp. SB67, while bacterial isolate 02 had a close relationship with Enterobacter cloacae strain CM 1 16S, bacterial isolate 03 was identified as Stenotrophomonas maltophilia and bacterial isolate 04 was a bacterium from the genus Bacillus which was closely related to Bacillus albus strain SQ30 16S.